AGE GROUPS OF SUBALKALINE BASIC DIKE OF THE EASTEN PART OF THE VOLHINIA MEGABLOCK OF THE UKRAINIAN SHIELD. - Omelchenko, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The occurrence and petrographic features of the subalkaline basic dike of the Volhynia Megablock are studyed. It has been established, that the investigated basic dikes are presented by the three age-groups that fundamentally differ of their geological position, age of intrusion and composition.